Higher education in Saudi Arabia : achievements, challenges and opportunities - Abouammoh, Abdulrahman; Smith, Larry (Higher Education Dynamics, 2013)
This book provides the first academically rigorous description and critical analysis of the Higher Education system in the Kingdom of Saudi Arabia, and of the vision, strategies and policy imperatives for the future development of Saudi universities. The government of Saudi Arabia has recognized in both policy and practice the necessity of developing its university system to world-class standard. Significantly increasing access and participation in Higher Education across a range of traditional and non-traditional disciplines is directly relevant to the future social and economic growth of the country. This book addresses the way in which Saudi Arabia is moving to develop a quality university system that balances the need for students to gain the knowledge, skills and 'ways of doing' necessary to operate effectively on the world stage while simultaneously maintaining and demonstrating the fundamental values of the Islamic religion and culture.  The book provides a description and critical analysis of the key components of the Saudi Higher Education system, and of system-level responses to the challenges and opportunities facing Saudi universities. It is written by a team of Saudi academics and authors of international standing from non-Saudi universities so as to provide both internal and external perspectives on all issues and to place information and ideas in the context of the international Higher Education scene.